Dual-polarization DBR fiber laser sensor for liquid-level measurement - Shum, Perry Ping (2013)
A dual-polarization distributed Bragg reflector (DBR) fiber grating laser for liquid level measurement is proposed and experimentally demonstrated. The laser cavity is used as the sensing device. The liquid level is obtained by measuring the beat frequency generated between the two lasing polarizaion modes. The result shows the beat frequency shifts linearly with the water level and a sensitivity of 241 kHz/mm has been obtained. The sensor is simple, easy to fabricate and with high sensitivity to liquid level variation, which could be very helpful in practical applications.